HIDROPONIK, SOLUSI CERDAS BERTANAM DI LAHAN SEMPIT PERKOTAAN - Siswadi, Siswadi (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2018)
The Community Harmony Activities entitled "Hydroponic Solutions in Narrow Lands" were held at the Ngubo Ammuktiwa Farmer Group of Kestalan Sub-District of Banjarsari Surakarta with the aim of increasing the understanding of how to solve the problems that occur in densely populated urban areas where the land is very narrow. Such conditions need to be a third-party assistance to provide a little touch of technology with the hope that the narrow land is able to provide power and maximum utilization that is with the cultivation of plants hydroponically. While the specific target to be achieved is if Activities Devotion To community is implemented then it is expected that the community will have skills in the field of hydroponics, especially vegetable hydroponics. To achieve these targets, the method of implementation is by lecturing and discussion followed by direct practice which is always monitored and evaluated periodically for 8 months. The implementation of Community Service Activities held on 26 March to 7 October 2017.Keywords: Hydroponics, narrow land.